Grassroots innovations and projectification: Diffusion processes of the European ecovillage movement - Girardi, A.; Kos, L.; Roysen, R.; Esteves, A. M.; Bruehwiler, N. (Environmental Policy and Governance, 2025)
Grassroots innovations are increasingly recognized as crucial actors in sustainability transitions, offering localized, bottom-up solutions to local and global challenges. These initiatives contribute to sustainability by diffusing sustainable innovations and practices to broader societal sectors. However, the functioning of grassroots innovations is influenced by projectification, that is, the structuring of efforts around temporary, grant-funded projects. Projectification has a significant impact on both the development and diffusion of grassroots innovations. This process also plays a key role in shaping the internal governance and functioning of grassroots innovations networks, influencing how these initiatives operate and evolve. Focusing on the European branch of the Global Ecovillage Network, we explore the interaction between projectification processes and the diffusion of ecovillage practices. Employing the embedding framework, we analyze how projects facilitate or constrain the diffusion of sustainable practices across and beyond the network. Methodologically, the research is based on in-depth fieldwork trips to three European ecovillages, resulting in 16 semi-structured interviews with ecovillage members and members of the European ecovillage network. Our findings indicate that while projects enable certain embedding processes, they also introduce tensions that could limit the long-term sustainability of these initiatives. This study underscores the need for a balanced approach to projectification, ensuring that it supports rather than undermines grassroots innovation's objectives.